Cometary origin of atmospheric methane variations on Mars unlikely. Issue 10 (17th October 2016) - Roos‐Serote, M.; Atreya, S. K.; Webster, C. R.; Mahaffy, P. R.
Abstract: The detection of methane in the atmosphere of Mars was first reported in 2004. Since then a number of independent observations of methane have been reported, all showing temporal variability. Up until recently, the origin of methane was attributed to sources either indigenous to Mars or exogenous, where methane is a UV degradation byproduct of organics falling on to the surface. Most recently, a new hypothesis has been proposed that argues that the appearance and variation of methane are correlated with specific meteor events at Mars. Indeed, extraplanetary material can be brought to a planet when it passes through a meteoroid stream left behind by cometary bodies orbiting the Sun. This occurs repeatedly at specific times in a planet's year as streams tend to be fairly stable in space. In this paper, we revisit this latest hypothesis by carrying out a complete analysis of all available data on Mars atmospheric methane, including the very recent data not previously published, together with all published predicted meteor events for Mars. Whether we consider the collection of individual data points and predicted meteor events, whether we apply statistical analysis, or whether we consider different time spans between high methane measurements and the occurrence of meteor events, we find no compelling evidence for any correlation between atmospheric methane and predicted meteor events. Key Points: Methane variations in the atmosphere of Mars are not correlated with predicted meteor events